2001
DOI: 10.1177/008124630103100403
|View full text |Cite
|
Sign up to set email alerts
|

A Lurian-Piagetian Approach to Assessment of Historically Disadvantaged Black Scholars in English Medium Schools

Abstract: Piagetian and Lurian assessment procedures were employed to evaluate the neurocognitive processes of seven-year-old historically disadvantaged children (n=27), residents of traditionally Black areas who were identified as experiencing learning problems (LP group) in English medium schools. Comparisons were made with a reference group of Black children in the same schools (n=23) currently not experiencing learning problems (NLP). No significant differences were found between factors such as maternal education, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…It was evident from all the studies that intelligence assessment instruments administered to South African school learners from diverse, demographic populations need to be applicable to that particular population subgroup, in order to be valid, reliable, and fair (Levert and Jansen, 2001;Reid et al, 2002;Jinabhai et al, 2004;De Beer, 2005;Jansen and Greenop, 2008;Ferrett, 2011;Teixeira, 2011;Mawila, 2012;Van Wyhe, 2012;Shuttleworth-Edwards et al, 2013;August, 2017;Mitchell et al, 2018). When administering imported western-developed intelligence instruments to South African school learners, appropriate and updated norms need to be applied, based on continuous normative studies conducted on an equivalent population group and within a similar context as the testees (Ferrett, 2011;Van Wyhe, 2012;Shuttleworth-Edwards et al, 2013;August, 2017).…”
Section: Theme 1: Applicability Of Intelligence Instruments Administe...mentioning
confidence: 99%
See 3 more Smart Citations
“…It was evident from all the studies that intelligence assessment instruments administered to South African school learners from diverse, demographic populations need to be applicable to that particular population subgroup, in order to be valid, reliable, and fair (Levert and Jansen, 2001;Reid et al, 2002;Jinabhai et al, 2004;De Beer, 2005;Jansen and Greenop, 2008;Ferrett, 2011;Teixeira, 2011;Mawila, 2012;Van Wyhe, 2012;Shuttleworth-Edwards et al, 2013;August, 2017;Mitchell et al, 2018). When administering imported western-developed intelligence instruments to South African school learners, appropriate and updated norms need to be applied, based on continuous normative studies conducted on an equivalent population group and within a similar context as the testees (Ferrett, 2011;Van Wyhe, 2012;Shuttleworth-Edwards et al, 2013;August, 2017).…”
Section: Theme 1: Applicability Of Intelligence Instruments Administe...mentioning
confidence: 99%
“…Some reviewed studies noted significant differences on intelligence assessment results among various South African school learner subgroups, and related performance differences to contextual and demographic influences (Levert and Jansen, 2001;Jinabhai et al, 2004;De Beer, 2005;Ferrett, 2011;Van Wyhe, 2012;Shuttleworth-Edwards et al, 2013;August, 2017;Mitchell et al, 2018). Some studies found that English school learners from an advantaged educational background performed at the highest level of all the subgroups tested (Ferrett, 2011;Van Wyhe, 2012;Shuttleworth-Edwards et al, 2013).…”
Section: Theme 2: Contextual and Demographic Influences Affecting Per...mentioning
confidence: 99%
See 2 more Smart Citations
“…Proficiency is encouraged in 'at least two languages' but the ability to converse or communicate in the other languages is also 'desirable ' (p. 14). Children in South Africa who come from disadvantaged backgrounds frequently attend schools where the language of learning and teaching medium differs from the home language (Levert & Jansen, 2000). Research findings suggest that such children are often at risk of school failure but the absence ofvalid assessment indicators can either prevent practitioners from making meaningful intervention or result in mislabelling or stigmatising outcomes (Jansen, 1998;Skuy, Taylor, O'Carroll, Fridjhon, & Rosenthal, 2000).…”
mentioning
confidence: 99%